2012
DOI: 10.1186/1479-5868-9-116
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic inequalities in occupational, leisure-time, and transport related physical activity among European adults: A systematic review

Abstract: BackgroundThis study systematically reviewed the evidence pertaining to socioeconomic inequalities in different domains of physical activity (PA) by European region.MethodsStudies conducted between January 2000 and December 2010 were identified by a systematic search in Pubmed, Embase, Web of Science, Psychinfo, Sportdiscus, Sociological Abstracts, and Social Service Abstracts. English-language peer-reviewed studies undertaken in the general population of adults (18–65 years) were classified by domain of PA (t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

35
380
6
28

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 435 publications
(449 citation statements)
references
References 144 publications
35
380
6
28
Order By: Relevance
“…Our results indicated that employees with higher educational levels tend to have more sedentary occupations, which is in accordance with the studies conducted on different populations [26,27]. In contrast, there was no significant relationship between educational level and the leisure-time or transport-related physical activity, although such relationships were previously determined in different populations [28]. Additionally, educational level was inversely related to the total and domestic physical activity, suggesting that the middle-aged employees with higher educational levels may be one of the priority target populations for physical activity promotion programs.…”
Section: Correlates Of Physical Activitysupporting
confidence: 71%
“…Our results indicated that employees with higher educational levels tend to have more sedentary occupations, which is in accordance with the studies conducted on different populations [26,27]. In contrast, there was no significant relationship between educational level and the leisure-time or transport-related physical activity, although such relationships were previously determined in different populations [28]. Additionally, educational level was inversely related to the total and domestic physical activity, suggesting that the middle-aged employees with higher educational levels may be one of the priority target populations for physical activity promotion programs.…”
Section: Correlates Of Physical Activitysupporting
confidence: 71%
“…Mesmo em delineamentos transversais, onde teoricamente não é possível a distinção de causa e efeito, a análise sobre a perspectiva da causalidade social aponta para a infl uência de aspectos demográfi cos e sociais sobre a presença de comportamentos de risco 19 , dentre eles, a inatividade física 20 .…”
Section: Discussionunclassified
“…No entanto, ainda há na literatura inconsistência sobre a associação entre o nível de escolaridade e a adoção do transporte ativo 5,15 . Recente estudo de revisão sistemática não observou evidência de associação do deslocamento ativo com o nível educacional, nem interação entre gênero e escolaridade 20 . É possível que fatores ambientais, como a conectividade das ruas, a densidade populacional, o trânsito, o uso misto do território e o planejamento dos bairros sejam especialmente importantes para o deslocamento ativo 29 .…”
Section: Discussionunclassified
“…Existing studies on socioeconomic inequalities in active transport provide inconsistent results [23]. For example, a Dutch study suggests that more educated adults are more likely to actively commute [24], whereas studies from the UK and Australia show the reverse [25][26][27].…”
Section: Introductionmentioning
confidence: 96%